Thyroid involvement in Chanarin-Dorfman syndrome in adults in the largest series of patients carrying the same founder mutation in ABHD5 gene - Nacim Louhichi; Emna Bahloul; Slaheddine Marrakchi; Houda Ben Othman; Chahnez Triki; Kawthar Aloulou; Lobna Trabelsi; Nadia Mahfouth; Zeineb Ayadi-Mnif; Leila Keskes; Faiza Fakhfakh; Hamida Turki (Orphanet Journal of Rare Diseases, 2019)
Abstract Background Chanarin-Dorfman syndrome (CDS) is a rare syndromic disease related to an accumulation of triacylglycerol in most organs. The aim of our study was to investigate various organs in a large series of CDS patients. Results We report for the first time thyroid function impairment in CDS. Among 12 investigated patients, 7 showed thyroid function impairment. All of them were over 30 of age. The 5 remaining investigated patients with normal thyroid function were under 30. Thyroid loss of function is an unknown clinical feature of CDS that could gradually develop with age. Thyroid ultrasound showed an abnormal aspect in all investigated patients (6 with thyroid impairment and 3 with normal thyroid function). Cervical MRI done in 2 patients with thyroid impairment showed fat infiltration of thyroid parenchyma. Audiogram carried out in 8 of our patients showed sensorineural hearing impairment in all patients, although only 2 patients suffered from clinical hypoacusia. We also demonstrated that kidney could be a more commonly involved organ than previously reported in the literature. A poorly differentiated kidney parenchyma is a common feature in our series. One patient showed cerebellar atrophy and T2 hypersignal of brain’s white matter in MRI. All patients carried the same founder mutation c.773(− 1)G > A in the ABDH5 gene. Discussion Aside from the congenital ichthyosiform erythroderma, the most common symptom of CDS, in addition to other organs involvement frequently reported in the literature, we described thyroid dysfunction, an unreported feature, probably related to the lipid infiltration of the thyroid parenchyma. The association found between age and hypothyroidism in CDS patients could explain the gradually development of thyroid disease with age. Conclusion We reported a thyroid dysfunction and unreported ultrasonographic aspects of kidneys and cerebral MRI in CDS patients. Methods We performed clinical analyses in 15 patients in whom thyroid, liver, ocular, kidney, skeletal muscle and neurological involvement were explored. Genetic and molecular explorations were performed by direct sequence analysis. Software SPSS, Fisher’s exact test and ANOVA were used for statistical analyses.